ANALISIS PELAYANAN PUBLIK DALAM PEMBUATAN KARTU PENCARI KERJA (AK-1) PADA DINAS TENAGA KERJA DAN TRANSMIGRASI KOTA DUMAI - Aprilia Nurhasanah Bakri; Latip (LPPM STIA Lancang Kuning Dumai, 2021)
The Dumai City Manpower and Transmigration Office is one of the government agencies that provides public services. Based on the observations made by the author, the symptoms of the problem are still found, namely there is still finding that service delivery is not in accordance with the stipulated time and there is still a lack of guarantee for the certainty of the completion time of the service that has been determined. The theory used according to Fitzsimmons and Fitzsimmons in Sinambela (2017:7), that there are five indicators of public services, as follows: (a) Reliability, (b) Tangibels, (c) Responsiveness, (d) Assurance and (e) Empathy. The population in this study were all employees in the Field of Training and Manpower Placement of the Department of Manpower and Transmigration as well as the community as many as 89 people. Sampling technique for employees using purposive sampling technique and the community using incidental sampling technique. The types of data in this study are primary data and secondary data. Data collection techniques by observation, questionnaires and interviews, while data analysis using descriptive statistics with rating scale measurements. The results of the research on Analysis of Public Services in Making Job Seeker Cards (AK-1) at the Dumai City Manpower and Transmigration Service can be categorized as quite good. This fact can be seen from 89 respondents obtained a score of 2,565 (64.04%) with a score range of 1,336-2,670. The supporting factors for Public Service in Making Job Seeker Cards (AK-1) at the Dumai City Manpower and Transmigration Office are: The ability of employees to communicate in providing services and There is a guarantee of the legality of the results of service products administratively While the inhibiting factors are: Still lack of employees who provide services according to the time set and there is still a lack of employees in providing services quickly. ABSTRAK Dinas Tenaga Kerja dan Transmigrasi Kota Dumai merupakan salah satu instansi pemerintah yang menyelenggarakan pelayanan publik. Berdasarkan observasi yang penulis lakukan, masih ditemukan gejala-gejala masalah, yaitu Masih ditemukannya pemberian pelayanan tidak sesuai dengan waktu yang ditetapkan dan Masih kurang terlaksananya jaminan kepastian waktu penyelesaian pelayanan yang telah ditetapan. Teori yang digunakan menurut Fitzsimmons dan Fitzsimmons dalam Sinambela (2017:7), bahwa terdapat lima indikator pelayanan publik, sebagai berikut: (a) Reliability, (b) Tangibels, (c) Responsiveness, (d) Assurance dan (e) Empathy. Populasi dalam penelitian ini adalah seluruh pegawai yang ada di Bidang Pelatihan dan Penempatan Tenaga Kerja Dinas Tenaga Kerja dan Transmigrasi serta masyarakat sebanyak 89 orang. Teknik pengambilan Sampel untuk pegawai menggunakan teknik Purposive sampling dan masyarakat menggunakan teknik insidental sampling. Jenis Data dalam penelitian ini adalah data primer dan data skunder. Teknik pengumpulan data dengan observasi, kuesioner dan wawancara, sedangkan analisis data menggunakan statistik deskriptif dengan pengukuran rating scale.Hasil penelitian Analisis Pelayanan Publik Dalam Pembuatan Kartu Pencari Kerja (AK-1) pada Dinas Tenaga Kerja dan Transmigrasi Kota Dumai dapat dikategorikan Cukup baik. Kenyataan ini terlihat dari 89 responden diperoleh skor 2.565 (64,04%) dengan rentang skor 1.336-2.670. Adapun faktor pendukung Pelayanan Publik Dalam Pembuatan Kartu Pencari Kerja (AK-1) pada Dinas Tenaga Kerja dan Transmigrasi Kota Dumai adalah: Terdapatnya kemampuan pegawai pada saat berkomunikasi dalam memberikan pelayanan dan Terdapatnya jaminan legalitas hasil produk pelayanan secara administratif Sedangkan faktor penghambat adalah: Masih kurangnya pegawai yang memberikan pelayanan sesuai dengan waktu yang ditetapkan dan Masih kurangnya pegawai dalam pemberian pelayanan dengan cepat.